2019
DOI: 10.1093/biolre/ioz192
|View full text |Cite
|
Sign up to set email alerts
|

Ablation of conceptus PTGS2 expression does not alter early conceptus development and establishment of pregnancy in the pig†

Abstract: Pig conceptuses secrete estrogens (E2), interleukin 1 beta 2 (IL1B2), and prostaglandins (PGs) during the period of rapid trophoblast elongation and establishment of pregnancy. Previous studies established that IL1B2 is essential for rapid conceptus elongation, whereas E2 is not essential for conceptus elongation or early maintenance of the corpora lutea. The objective of the present study was to determine if conceptus expression of prostaglandin-endoperoxide synthase 2 (PTGS2) and release of PG are important … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 66 publications
3
23
0
Order By: Relevance
“…This indicated a new role for PGF2α secreted by the conceptuses and endometrium in supporting pregnancy establishment during the implantation period. However, the depletion of the rate-limiting enzyme prostaglandin-endoperoxide synthase 2 ( PTGS2 or COX2 ) in conceptus had no effect on either PGF2α and PGE contents in the uterine flushings or conceptus elongation in pigs ( Pfeiffer et al., 2020 ). Whether ROS were involved in this process remains unknown.…”
Section: Activation Of Redox Pathways In Porcine Conceptus Trophectodermmentioning
confidence: 99%
“…This indicated a new role for PGF2α secreted by the conceptuses and endometrium in supporting pregnancy establishment during the implantation period. However, the depletion of the rate-limiting enzyme prostaglandin-endoperoxide synthase 2 ( PTGS2 or COX2 ) in conceptus had no effect on either PGF2α and PGE contents in the uterine flushings or conceptus elongation in pigs ( Pfeiffer et al., 2020 ). Whether ROS were involved in this process remains unknown.…”
Section: Activation Of Redox Pathways In Porcine Conceptus Trophectodermmentioning
confidence: 99%
“…Inhibition of PG synthesis by PTGS2, the dominant cyclooxygenase enzyme in both the conceptus and endometrium, prevents conceptus elongation and results in pregnancy loss [215,216,220]. However, recent studies in other species have suggested that embryonic production of PGs is not required for early pregnancy success [229,231,232]. In Chapter Five, One important question that remains is how lipids are mobilized or transported within the ULF due to their hydrophobic nature.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, endometrial PG are more important than embryonic PG production in early pregnancy in mice [229][230][231]. Recent work in the pig has also demonstrated that conceptus-derived PG are not required for early conceptus development and can maintain pregnancy beyond day 30 [232]. Thus, while PG are undoubtedly critical regulators of conceptus elongation, the importance of conceptus production of PG in ruminant species is unclear.…”
Section: Prostaglandins In the Uterine Lumenmentioning
confidence: 99%
“…Despite the decreased PG synthesis, PTGS2 -/conceptuses were able to elongate, establish pregnancy, and maintain pregnancy to day 35 of gestation. Although PTGS2 -/-PG production was significantly decreased on day 14 and 17 of pregnancy, uterine lumen flush (ULF) content of PG was not affected (Pfeiffer et al 2019). ULF content of PG was expected to be similar between control and edited conceptus pregnancies as the maternal endometrium is the major contributor of PG into the uterine lumen.…”
Section: Prostaglandin Role In Maternal Recognition Of Pregnancymentioning
confidence: 99%
“…Extracted RNA was treated with RNase Free DNase Set (Qiagen, 79256) to eliminate genomic DNA contamination. Quantity and quality of RNA and DNA in the samples were established by using a NanoDrop ND-1000 spectrophotometer and visualization of conceptus DNA bands on a 2% ethidium bromide agarose gel and RNA with a 1% ethidium bromide agarose and a 1% bleach integrity gel as previously described (Pfeiffer et al 2019).…”
Section: Total Rna Genomic Dna and Protein Isolationmentioning
confidence: 99%